2019
DOI: 10.1186/s13102-019-0143-7
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity promotion in daily exercise therapy: the perspectives of exercise therapists in German rehabilitation settings

Abstract: BackgroundThis study aims to explore exercise therapists’ perspectives on the topic of physical activity promotion (PAP) with a focus on identifying (i) the intervention content and methodological approaches used for promoting physical activity (PA) in daily practice and (ii) the barriers and facilitators that affect PAP.MethodsThis qualitative study comprised the heads of exercise therapy departments (n = 58; 41% women; mean age = 45 years) from different rehabilitation clinics in Germany. Each participant to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 52 publications
0
19
0
3
Order By: Relevance
“…Rehabilitation and physical activity are closely related; in fact, the former promotes the latter [ 55 ]. Thanks to this relationship, the positive effect of L-carnitine supplementation on physical performance could also be found in rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation and physical activity are closely related; in fact, the former promotes the latter [ 55 ]. Thanks to this relationship, the positive effect of L-carnitine supplementation on physical performance could also be found in rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, exercise therapy based on frameworks of behaviour change is lacking within German rehabilitation [ 28 ]. BET, as conceptualised by [ 29 ], goes beyond a mere biomedical approach by addressing personal context factors such as the above-mentioned psychosocial factors in individuals with CLBP [ 18 , 26 ] and systematically integrates behaviour change techniques [ 30 ] to promote physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…We applied focus group discussions, as these are suitable for capturing complex attitudes in multi-layered subject areas. A detailed description of the qualitative part of the study can also be found at Geidl et al [23]. As part of the two workshops, semi-structured focus groups on various exercise therapy topics with a focus on physical activity promotion took place in April 2016 with exercise therapy practitioners for the health conditions Orthopedics back, Orthopedics total hip/knee replacement, Neurology, Oncology, Psychosomatics, and Addiction.…”
Section: Qualitative Part Of the Study 231 Design And Implementationmentioning
confidence: 99%
“…A total of 58 persons (24 women, 34 men) aged between 28 and 61 (M = 45; SD = 10) took part. A detailed overview of the characteristics of the participants of the qualitative part of the study can be found at Geidl et al [23].…”
Section: Samplementioning
confidence: 99%